The role of cognitive and metacognitive factors in non‐clinical paranoia and negative affect. (5th October 2017) - Sellers, Rachel; Emsley, Richard; Wells, Adrian; Morrison, Anthony P.
Abstract : Objectives: It is increasingly accepted that paranoia lies on a continuum of severity that can be observed in the general population. Several psychological factors have been implicated in the development of more distressing persecutory ideas including negative affect (i.e., anxiety and depression), beliefs about oneself and other people (i.e., schemas), and metacognitive beliefs. This study aimed to explore the combined role of cognition and metacognition in paranoia. Specifically, unhelpful metacognitive beliefs and schematic beliefs were tested as potential moderators of the relationship between non‐clinical paranoid ideation and negative affect. Methods: Measures from 227 people who took part in a cross‐sectional online survey were analysed using structural equation modelling. A series of models grounded in cognitive and metacognitive theory were tested sequentially. Results: The results demonstrated that unhelpful metacognitive beliefs had a positive moderating effect on the relationship between paranoia and negative affect. Negative beliefs about oneself and other people did not moderate negative affect but positive beliefs about other people had a negative moderating effect. In a final model, negative schematic beliefs predicted paranoid ideation whilst metacognitive beliefs predicted and moderated affect. Conclusions: The findings suggest that consideration of metacognitive beliefs, as well as schemas, may be important in understanding non‐clinical paranoia. Practitioner points: Metacognitive beliefs may be an important determinant of negative affect in the context of non‐clinical paranoia. The consideration of both cognitive and metacognitive factors may be helpful when working with people with distressing paranoid ideas.